Products innovation in Islamic finance Workshop in Islamic Economics and Finance 2009 (WIEF'09), Bilik Seminar, Pusat Penerbitan dan Percetakan, Universiti Kebangsaaan Malaysia, 30-31 March 2009 - Workshop in Islamic Economics and Finance (2009 : Bangi, Selangor).; Abdul Ghafar Ismail; Achmad Tohirin; Mohamad Abdul Hamid; Universiti Kebangsaan Malaysia. Fakulti Ekonomi dan Perniagaan (Bangi : Fakulti Ekonomi Dan Perniagaan, Universiti Kebangsaan Malaysia, 2009)
Contains 20 papers presented in Workshop in Islamic economics and finance 2009.
Title from main page
PTSL : 2009
System requirements: Adobe Acrobat Reader.
Keywords: Finance -- Islamic countries -- Congresses; Finance -- Religious aspects -- Islam -- Congresses; Banks and banking -- Religious aspects -- Islam -- Congresses